“I guess I need to say something about it at some point, maybe”: Sexual recidivism and the narrative negotiation of anticipated stigma management - Sandbukt, Ingeborg Jenssen (Punishment & society, 2025)
Individuals convicted of child sexual offenses face one of the most stigmatized labels in modern society. Their ability to hide this label is restricted, even in countries without public registration or notification. This study explores how anticipated stigma influences men who have reoffended sexually in their preparations for community reentry. Nineteen currently incarcerated “sexual recidivists” were interviewed twice using McAdams' Life Story Interview, supplemented by questions that invited reflections on identity, stigma, and stigma management. Drawing on modified labeling theory, reflexive thematic analysis was used to explore their negotiation of anticipated stigma management. The results show that stigma had a disruptive effect on the men's narratives about the future, that their negotiation of stigma management strategies took the form of a cost–benefit analysis, and that in the absence of a formula for preventive telling, preventive behavior manifested as a future strategy. These findings are discussed in terms of desistance, redemption scripts, and society's lack of language in this regard.